Distribution and phospholipase activity of Candida species in different denture stomatitis types - KADİR, TANJU (SPRINGER, 2006)
The aim of this study was to evaluate the correlation between frequency and phospholipase activity of Candida species and denture stomatitis according to Newton's classification. Seventy-five complete denture wearers were evaluated for the presence of yeasts on the palatal mucosa by culture method. In addition, the number of yeast isolates producing phospholipase and amount of this enzyme were determined using egg yolk agar plate method. According to Newton's classification, 25 denture wearers were with healthy palatal mucosa while 50 were with any types of denture stomatitis. The frequency of yeasts was linked to whether subjects had Type II or Type III, but not Type I denture stomatitis. Candida albicans was the most frequently isolated species in denture wearers with and without clinical signs of denture stomatitis and it was the only species produced phospholipase. Although the amount of phospholipase produced by the C. albicans isolates from denture wearers in control and Type II and III DS groups was not significantly different, there was statistically significant difference in the number of C. albicans isolates producing phospholipase between patients with and without clinical signs of DS.
Keywords: Candida; denture stomatitis; phospholipase activity; ORAL MUCOSAL LESIONS; VIRULENCE FACTORS; ALBICANS; PATHOGENICITY; PEOPLE; STRAIN